Advantages of Herbal Over Allopathic Medicine in the Management of Kidney and Urinary Stones Disease - Saurabh Nimesh; Vrish Dhwaj Ashwlayan; Rubi Rani; Om Prakash (Borneo Journal of Pharmacy, 2020)
Kidney and urinary stone disease (Nephrolithiasis and urolithiasis) are the condition where urinary stones or calculi are formed in the urinary tract. The problem of urinary stones is very ancient; these stones are found in all parts of the urinary tract, kidney, ureters, and the urinary bladder and may vary considerably in size. It is a common disease estimated to occur in approximately 12% of the population, with a recurrence rate of 70-81% in males and 47-60% in females. The treatment of kidney and urinary stone diseases such as a western (allopathy) medicine and surgery is now in trends. However, most people preferred plant-based (herbal) therapy because of the overuse of allopathic drugs, which results in a higher incidence rate of adverse or severe side effects. Therefore, people every year turn to herbal therapy because they believe plant-based medicine is free from undesirable side effects, although herbal medicines are generally considered to be safe and effective. In the present article, an attempt has been made to emphasize an herbal therapy is better than allopathic therapy for the management of the kidney and urinary stone disease.